Abdominal Compartment Syndrome - Pınar Zeyneloğlu (Galenos Yayinevi, 2015)
Intraabdominal hypertension and Abdominal compartment syndrome are causes of morbidity and mortality in critical care patients. Timely diagnosis and treatment may improve organ functions. Intra-abdominal pressure monitoring is vital during evaluation of the patients and in the management algorithms. The incidence, definition and risk factors, clinical presentation, diagnosis and management of intraabdominal hypertension and Abdominal compartment syndrome were reviewed here.